Pengembangan E-LKPD Berbasis Discovery Learning Pada Materi Usaha dan Energi Kelas X SMA Swasta Gajah Mada Medan - Herna Puspita Padang; Irham Ramadhani (Universitas Pendidikan Mandalika, 2026)
This study aimed to develop and evaluate a Discovery Learning-based interactive E-LKPD (Elektronik-Lembar Kerja Peserta Didik/Electronic Student Worksheet) for teaching work and energy in Grade X senior high school physics. The study employed a research and development design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 30 Grade X students at SMA Swasta Gajah Mada Medan, including 10 students in a small-group trial and 20 students in a large-group trial. Data were collected through expert validation sheets, teacher and student response questionnaires, observation sheets, and a 20-item learning outcome test. Product validity was examined using expert judgment and Cohen’s Kappa, practicality was analyzed using response percentages, and potential effectiveness was evaluated through pretest-posttest analysis, paired-samples t-test, Cohen’s d, and normalized gain. The results showed substantial agreement among validators, with Cohen’s Kappa of 0.674. The overall practicality score reached 86.0%, indicating a practical category. Students’ mean score increased from 48.5 on the pretest to 93.0 on the posttest, with t(19) = 18.42, p < 0.001, Cohen’s d = 2.31, and N-gain = 0.86. These findings indicate that the developed E-LKPD is valid, practical, and has potential effectiveness for supporting students’ learning of work and energy concepts.